The bacterial aetiology of adult community-acquired pneumonia in Asia: a systematic review. - Peto, L; Nadjm, B; Horby, P; Ngan, T; van Doorn, R; Van Kinh, N; Wertheim, H (Elsevier, 2014)
BACKGROUND: Community-acquired pneumonia (CAP) is a major cause of adult mortality in Asia. Appropriate empirical treatment depends on knowledge of the pathogens commonly responsible. However, assessing the aetiological significance of identified organisms is often difficult, particularly with sputum isolates that might represent contamination with oropharyngeal flora. METHODS: A systematic review of all adult CAP aetiology studies from Asia, excluding the Middle East, published in English between 1 January 1990 and 1 March 2012 was conducted. Forty-eight studies reporting on 10 423 patients were included, representing data from China, India, Indonesia, Japan, Malaysia, The Philippines, Singapore, South Korea, Taiwan, Thailand and Vietnam. Data from large parts of Asia were unavailable and there was substantial heterogeneity in methodology. RESULTS: As in western studies, Streptococcus pneumoniae, Mycoplasma pneumoniae, Chlamydophila pneumoniae, Legionella spp. and Haemophilus influenzae were all significant pathogens. However, compared with western studies, S. pneumoniae was of less relative importance. Gram-negative bacilli and Mycobacterium tuberculosis were more important, and in northeast Thailand Burkholderia pseudomallei was a major pathogen. CONCLUSION: These data have major implications for diagnostic strategies and empirical treatment. Narrow-spectrum antibiotics targeting S. pneumoniae may be inappropriate in many Asian settings, and agents active against TB may lead to partial response and delayed TB diagnosis.